Výzkum v didaktice cizích jazyků V - Hradílková, Helena (Masaryk University Press, 2022)
Title in English: Research in foreign language didactics V This publication presents an empirical research of pronunciation mistakes of Czech students learning German as a second foreign language at elementary school. The aim of the research was to verify the extent of the students' pronunciation difficulties with German pronunciation phenomena error-prone for Czech native speakers. The research determined in what way these errors manifest themselves in the transfer from the students' previously acquired languages, i.e. their mother tongue (Czech) and the first foreign language learnt (English). Within the theoretical foundation, the focus is put on different concepts of pronunciation in terms of foreign language teaching objectives, definitions of language errors and their causes, the development of the German pronunciation standard and methodological approaches to error analysis.